Motivation communication training programme for healthcare professionals to support adherence in patients with diabetic foot ulcers: Proof of concept study. - Jennie E Hancox; Wendy J Chaplin; Charlotte E Hilton; Noemi Vadaszy; Katie Gray; Fran Game; Kavita Vedhara (PLoS ONE)
Patients with diabetic foot ulcers have poor adherence to treatment recommendations. However, the most effective way to support adherence in this population is unknown. This study aimed to assess the preliminary effectiveness of a motivation communication training programme for healthcare professionals working with these patients, using theory and evidence-based strategies.A proof-of-concept study using a non-randomised, controlled before-and-after design. Six podiatrists took part in the motivation communication training programme. Pre-training, observation was undertaken to examine the communication style currently used by podiatrists in routine consultations. Patients' (n = 25) perceptions of podiatrist autonomy support, self-determination for limiting weight-bearing activity and average daily step count were also assessed. Post training, observations and patient measures were repeated with a different group of patients (n = 24). Observations indicated that podiatrists exhibited a more need-supportive communication style (e.g., taking time to understand patients' perspectives) after undergoing the training programme. Patients in the post-training group reported higher levels of autonomy support, while self-determination to limit weight-bearing activity remained unchanged. Although the post-training group had a lower average daily step count, the difference was not statistically significant. This is the first study to investigate implementation of motivation communication strategies in routine consultations with patients with diabetic foot ulcers. Results suggest that training can enhance healthcare professionals' motivation communication skills with potential for addressing adherence issues, however, a larger cluster randomised controlled trial is necessary to confirm this.